Seroprevalence of antibodies to dengue and chikungunya viruses in Thailand. - Sompong Vongpunsawad; Duangnapa Intharasongkroh; Thanunrat Thongmee; Yong Poovorawan (PLoS ONE)
The abundance of Aedes mosquito species enabled widespread transmission of mosquito-borne chikungunya virus (CHIKV) and dengue virus (DENV) in Southeast Asia. Periodic seroprevalence surveys are therefore necessary to assess the viral burden in the population and the effectiveness of public health interventions. Since the current seroprevalence for CHIKV and DENV in Thailand are unknown, we evaluated evidence of past infection among Thais. Eight-hundred and thirty-five serum samples obtained from individuals living in central and southern Thailand were assessed for anti-CHIKV and anti-DENV IgG antibodies using commercial enzyme-linked immunosorbent assays. Overall, 26.8% (224/835) of individuals were seropositive for CHIKV, the majority of whom were also DENV-seropositive (91.1%, 204/224). Approximately half of all adults in their fifth decade of life had attained CHIKV seropositivity. Children under 15 years of age in southern Thailand were significantly more likely to be CHIKV-seropositive compared to those residing in central Thailand. In contrast, 79.2% (661/835) of Thais were DENV-seropositive, 30.9% (204/661) of whom also had antibodies to CHIKV. CHIKV/DENV dual seropositivity among Thais was 24.4% (204/835). The age-standardized seroprevalence for DENV was three times that of CHIKV (80.5% vs. 27.2%). Relatively high CHIKV seroprevalence among adults living in central Thailand revealed an under-recognized CHIKV burden in the region, while the low-to-moderate transmission intensity of DENV (seroprevalence <50% at 9 years) is expected to reduce the impact of DENV vaccination in Thailand. This most recent seroprevalence data provide serological baselines for two of the most common mosquito-borne viruses in this region.